Women, Homeland and Memories: Feminist Yan Geling’s Writings - Katherina Li (Space and Culture, India, 2023)
Yan Geling, a feminist of Chinese origin, is a gifted and successful storyteller and creator of characters. However, despite a widespread contribution, Yan Geling’s writings are not popular in the West and remain in a marginalised position. A qualitative case study of Yan Geling’s writings will fill in the literature gap to understand those marginalised Chinese women’s voices. This study examines the work of Yan Geling by applying various observations and data sources. It concentrates on her depiction of her homeland: her fiction takes place in realistic settings during the turbulent years of the 20th Century. Nevertheless, Yan Geling’s works,  particularly her writings on women’s situations using a feminist lens, have rapidly increased in recent years. This perspective is an attempt to reflect on Yan Geling’s novel, the analysis of which are more likely to contribute to future Chinese feminist studies.